Evaluation of Small Intestinal Permeability in Patients with Overlap Syndrome (Autoimmune Hepatitis/Primary Biliary Cholangitis) - D. R. Akberova; A. Kh. Odintcova; D. I. Abdulganieva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to evaluate the state of small intestine permeability by the “double sugar test” in patients with overlap syndrome (autoimmune hepatitis / primary biliary cholangitis (AIH / PBC)).Materials and methods. Prospectively, 56 people were included in the study. Of these, 26 were diagnosed with AIH/PBC, 30 were in the control group. The diagnosis was made in accordance with the current recommendations. The average age of patients was 49.7 ± 13.8 years, healthy volunteers — 48.6 ± 9.2 years. The determination of the permeability of the small intestine was carried out by a “double sugar test” (the ratio of lactulose/mannitol in urine), using the method of high-performance liquid chromatography — mass spectrometry.Results. In patients with AIH/PBC, an increase in intestinal permeability was found — 0.20 [0.09; 0.30] (p < 0.001) compared with the control group 0.01 [0.01; 0.02]. We divided patients at the stage of liver damage. An increased small intestinal permeability was revealed: hepatitis stage — 0.19 [0.13; 0.30] (p < 0.001), liver cirrhosis stage — 0.18 [0.09; 0.30] (p < 0.05) compared with the control group. In the early stages of disease (1 month from the onset of the disease) had an increased lactulose/mannitol ratio — 0.13 [0.05; 0.26] (p < 0.001) compared to the control group. In the presence of portal hypertension (PH), small intestinal permeability was increased — 0.18 [0.09; 0.30] (p < 0.001) compared with the control group.Conclusions. An increase in small bowel permeability was found in patients with overlapping syndrome. All patients had increased intestinal permeability (regardless of the presence of extrahepatic manifestations).